PENGEMBANGAN TES DIAGNOSTIK FOUR TIER TEST TENTANG MATERI TEKANAN ZAT SMP NEGERI DI PONTIANAK - Syintia, Syintia; TMS, Haratua; Oktavianty, Erwina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
Abstract This study was intended to conduct a four-level test that is feasible on substance pressure material for the students ' misconceptions. This study uses the four-level research and development (R&D) method. The development of the test took the step of developing Borg & Gall which had been simplified into 7 steps. This research was conducted in SMP Negeri Kota Pontianak. The initial design of the test consisted of 20 multiple-choice questions. Trial questions about 34 students on a small scale test, and 88 students on a large scale trial. Based on data analysis, it can be concluded that the developed test is appropriate to be used to correct students' misconceptions based on the test eligibility criteria, namely: 1) has a higher validity than the validity of the table that is ? 0.2096, 2) has a corresponding average reliability that is ? 0, 81, 3) all test items can support students' misconceptions, 4) have a moderate level of appropriateness with a value ? 0.69, 5) an overall readability level of 3.08. The four-level educational test that is developed is appropriate for students to use misconceptions. Keywords : Diagnostic Test, Four Tier Test, Pressure Substance